17‐beta‐estradiol analog inhibits cell proliferation by induction of apoptosis in breast cell lines. Issue 3 (22nd January 2014) - Visagie, Michelle Helen; Birkholtz, Lynn‐Marie; Joubert, Anna Margaretha
ABSTRACT Microtubules are important targets when studying potential anticancer agents since disturbance of these microtubule dynamics results in cell cycle arrest and cell death. 2‐Methoxyestradiol is a naturally occurring metabolite that exerts antiproliferative activity and induces apoptosis. Due to limited biological accessibly and rapid metabolic degradation, several analogs were synthesized. This study investigated the antiproliferative influence of an 2‐methoxyestradiol analog, (8R, 13S, 14S, 17S)‐2‐Ethyl‐13‐methyl‐7, 8, 9, 11, 12, 13, 14, 15, 16, 17‐decahydro‐6H‐cyclopenta[a]phenanthrane‐3, 17‐diyl bis(sulfamate) (EMBS) on cell proliferation, morphology and apoptosis induction in a estrogen receptor‐positive breast adenocarcinoma cells line (MCF‐7), estrogen receptor‐negative highly metastatic breast cell line (MDA‐MB‐231) and a non‐tumorigenic breast epithelial cell line (MCF‐12A). Spectrophotometry results indicated that EMBS exerted differential antiproliferative activity in the three cell lines. Cell growth of the breast adenocarcinoma and highly metastatic breast cell line reached a plateau effect at 0.4 μM after 24 h of exposure. Light microscopy and polarization‐optical transmitted light differential interference contrast demonstrated compromised cell density, cells blocked in metaphase and the presence of apoptotic characteristics after EMBS exposure for 24 h in all three cell lines. Transmission electron microscopy and scanning electron microscopy revealed hallmarks of apoptosis namely the presence of apoptotic bodies, shrunken cells and cell debris in EMBS‐exposed cells. This investigation demonstrated that EMBS does exert antimitotic activity and induces apoptosis contributing to elucidating the signal transduction of EMBS in tumorigenic and non‐tumorigenic breast cell lines. Findings warrant in‐depth analysis of specific targets in vitro and subsequent in vivo investigation for anticancer therapy. Microsc. Res. Tech. 77:236–242, 2014. © 2014 Wiley Periodicals, Inc.